Exploring Ethical Cosmopolitanism Through Tongkonan Symbolism: A Hermeneutic Perspective on the Toraja Community - Oktoviandy Oktoviandy; Lobby Loekmono; Izak YM. Lattu; Suwarto Suwarto (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2025)
Previous studies have often regarded the tongkonan solely as a traditional, primordial symbol tied exclusively to Toraja culture. This article challenges that view by exploring the broader, transnational ethical dimensions of the tongkonan symbolism, which have not been fully addressed in existing literature. This research aims to empirically examine the relationship between individual subjects, the Toraja community, and other global communities, integrating these findings into a holistic, cosmopolitan perspective. Adopting a qualitative approach with a hermeneutic framework, this study analyzes the tongkonan as a cultural text through the lenses of symbol theory and ethical cosmopolitanism. Six informants participated in the study, consisting of two customary leaders, a church official, a religious leader, an educational practitioner, and a tongkonan carver. Data were collected through unstructured interview and observation. The research findings demonstrate that the symbolism of the tongkonan, understood as a representation of the microcosm, aligns with the principles of ethical cosmopolitanism, particularly in terms of cosmic brotherhood or fraternity. The Toraja people, through their symbolic use of the tongkonan, have historically positioned themselves as cosmopolitans or world citizens. The tongkonan embodies an ideal type of human being—one who is guided by solidarity and a sense of responsibility towards the liyan (fellow beings), thus reflecting a cosmopolitan personality. These results confirm the congruence between the symbolic meaning of the tongkonan and the tenets of ethical cosmopolitanism, indicating that the Torajan people have embraced their identity as global citizens, ethically connected across transnational scales.